PAC identification of electric-nuclear-quadrupole interactions in Sm-sesquioxides - Rentería, Mario (2000)
We present Perturbed Angular Correlation (PAC) results of the electric-nuclear quadrupole interaction at 181Ta located at the nonequivalent cation sites of cubic C-Sm2O3 and monoclinic B-Sm2O3 free of defects. The application of the empirical Cd/Ta correlation found in binary oxides allowed us to correlate the interactions with each site and to identify the single Sm site populated in 111In-implanted B-Sm2O3 experiments. The preferential site occupation of Cd and Ta in B-Samaria is discussed in terms of the "chemistry" of the probe-atoms.